Web scraping with Python : collecting data from the modern web (O'Reilly Media, 2015)
Learn web scraping and crawling techniques to access data from any web source in any format. Teaches basic web scraping mechanics, but also delves into more advanced topics, such as analyzing raw data or using scrapers for frontend website testing.